Kepemimpinan Mudir di Pondok Pesantren Kampung Qur’an Kecamatan Cimanggung Kabupaten Sumedang Jawa Barat - Ali Amin; Ahmad Ridwan; Riyadul Jannah (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Islamic boarding schools are one of the Islamic educational institutions as a place to study and explore Islamic teachings. The progress of Islamic boarding schools is largely determined by the type of leadership used by a leader. The purpose of this study was to determine the leadership concept of Islamic boarding schools in Kampung Qur'an, Cimanggung sub-district, Sumedang district, West Java. This study uses a descriptive qualitative approach. The focus of this research is to explore the leadership style of the Qur'an village Islamic boarding school. The research data was collected through interview, observation, and documentation techniques. The results of this study indicate that the leadership style in Islamic boarding schools Kampung Qur'an, Cimanggung District, Sumedang Regency, West Java, the most dominant is the democratic leadership style